2009
DOI: 10.1097/sla.0b013e3181a334f9
|View full text |Cite
|
Sign up to set email alerts
|

The Vessel Sealing System (LigaSure) in Hepatic Resection

Abstract: This randomized controlled trial showed that while the vessel sealing system was safe, its use was not associated with any significant decrease of the operation time or blood loss during liver transaction as compared with that of the clamp crushing method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 24 publications
3
85
1
2
Order By: Relevance
“…Во всех других публикациях отмечается уменьшение объема кровопотери во время операции, отсутствие в после-операционном периоде кровотечений и подтеканий желчи [21] или снижение числа таких осложнений, а также уменьшение времени диссекции паренхимы и улучшение восстановления пациентов в послеопера-ционном периоде [22][23][24][25]. Но в рандомизированном исследовании Ikeda M. et al отмечается отсутствие различий в объеме кровопотери и времени диссекции паренхимы при применении аппарата «LigaSure» и ме-тодики «Clamp-crush» при среднем времени диссек-ции около 1 ч [26].…”
Section: Discussionunclassified
“…Во всех других публикациях отмечается уменьшение объема кровопотери во время операции, отсутствие в после-операционном периоде кровотечений и подтеканий желчи [21] или снижение числа таких осложнений, а также уменьшение времени диссекции паренхимы и улучшение восстановления пациентов в послеопера-ционном периоде [22][23][24][25]. Но в рандомизированном исследовании Ikeda M. et al отмечается отсутствие различий в объеме кровопотери и времени диссекции паренхимы при применении аппарата «LigaSure» и ме-тодики «Clamp-crush» при среднем времени диссек-ции около 1 ч [26].…”
Section: Discussionunclassified
“…These tools were initially thought to be the main reason for this decreased blood loss during LLR and are now frequently used during open surgery. However, the superiority of new hemostatic devices for parenchymal transection over the conventional clamp crushing method [50] has yet to be demonstrated. Lesurtel et al [49] conducted a prospective randomized study comparing four different transection strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Several surgical procedures can decrease blood loss and the need for transfusion considerably during liver surgery: the use of low central venous pressure [48], new hemostatic devices for parenchymal transection [49,50], and the control of vascular inflow [49,51] and outflow [52] before liver division. Our review shows that, in LLR these non-specific procedures are as efficient as they are in open approach.…”
Section: Discussionmentioning
confidence: 99%
“…A: BVSD coagulates sealing vessels up to 7 mm in diameter with minimal charring, thermal spread or smoke, it's capable to reduce blood loss and the need for vessel occlusion techniques if compared to traditional techniques [8], [71], [72], A recently published randomized controlled trial demonstrated that the use of Ligasure in combination with a clamp crushing technique resulted in lower blood loss and faster transaction speed in minor liver resections compared with the conventional technique of electric cautery or ligature for controlling vessels in the transection plane [73]. Otherwise a more recent randomized trial from the same team was not able to show a real difference between the traditional techniques and the Ligasure vessel sealing system [74]. The instrument is available for both laparotomic and laparoscopic surgery [75].…”
Section: Dmentioning
confidence: 99%
“…They considered 3 mm as the range of maximal effectiveness in sealing portal triads (without increasing the rate of biliary fistula). A more recent randomized study [74] did not demonstrate this difference in blood loss, operating time and hospital stay, failing to find a superiority of one technique over the other. In this particular situation, the cost-effectiveness of LigaSure in the clamp-crush method was not confirmed, favoring once again the latter.…”
Section: Comparison Of Different Liver Transection Techniquesmentioning
confidence: 99%